Application of seven tools for evaluation of greenness of chromatographic methods for Remdesivir analysis - Aesha Bhalodia; Sonal Desai (Green Analytical Chemistry)
Green analytical chemistry is concerned with making analytical techniques more secure and environmentally friendly. A crucial aspect of this approach is the assessment of the greenness of analytical methods. Remdesivir, a SARS-CoV-2 nucleotide analog RNA polymerase inhibitor, has been authorized by USFDA as the initial course of therapy for hospitalized COVID-19 patients. The proposed study evaluates greenness of several reported chromatographic methods for estimation of Remdesivir using seven different tools namely ComplexGAPI, BAGI, AGREE, AGREEprep, AMGS, ChlorTox and RGBfast.